Corruption's impact on foreign portfolio investment. Issue 1 (February 2017) - Jain, Pankaj K.; Kuvvet, Emre; Pagano, Michael S.
Highlights: Corruption is associated with decreases in liquidity and foreign portfolio investment. The effects of corruption on foreign investment are nonlinear and reverse J-shaped. Intermediate levels yield the most negative effects. Highly transparent nations and very corrupt countries both attract more foreign investment. The nonlinear pattern is consistent with foreign investors' desire to trade in markets where they are not at an informational disadvantage. Abstract: Corruption has significant effects on a nation's financial markets through its adverse impact on foreign portfolio investment (FPI). Yet, the effects of corruption on FPI are nonlinear and reverse J-shaped, with intermediate levels of corruption yielding the most negative effects. Highly transparent nations, where a "level playing field" exists between foreign and local investors due to lack of information asymmetries related to corruption, attract the most foreign investment. However, at the margin, very corrupt countries attract more investment than moderately corrupt countries because a "perverse level playing field" in the former countries may put foreigners and locals on an even footing in terms of resolving asymmetric information problems. This nonlinear pattern is consistent with foreign investors' desire to trade in markets where they are not at an informational disadvantage.